RANCANG BANGUN SISTEM INFORMASI PRESENSI PEGAWAI DENGAN MEMANFAATKAN METODE PENGEMBANGAN PROTOTYPE - Eva Meilinda (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2021)
The diligence of employees is an important factor for agencies and businesses to achieve their goals, it is related to discipline and affects the work performance of each employee. Therefore, it is necessary to collect special data for attendance records so that work activities can be recorded accurately and in real time. There are many ways to implement a good attendance and attendance information system, one of which is using computer technology applied to web-based attendance and attendance applications. As a case study and research site, at CU. The source of love City Balai Berkuak was originally used in the process of presence with the help of fingerprints, because during a pandemic like this it is still not effective, because it is possible to spread the covid19 virus. In addition, the risk of errors and loss of attendance data is quite large. Based on the above issues, an employee attendance information system has been built at UC. The origin of love but the Berkuak room. Research methods used to collect data include: observation, interview and library research methods. Software development using the prototyping method. With the results web-based employee attendance system, it can simplify the attendance process, data search and time summary calculation, as well as minimize loss and error when recording employee data presence of CU. The origin of love but the Berkuak room.